2000
DOI: 10.1073/pnas.97.7.3661
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of use-dependent plasticity in the human motor cortex

Abstract: Practicing movements results in improvement in performance and in plasticity of the motor cortex. To identify the underlying mechanisms, we studied use-dependent plasticity in human subjects premedicated with drugs that influence synaptic plasticity. Use-dependent plasticity was reduced substantially by dextromethorphan (an N-methyl-d-aspartate receptor blocker) and by lorazepam [a gamma-aminobutyric acid (GABA) type A receptor-positive allosteric modulator]. These results identify N-methyl-d-aspartate recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 479 publications
(66 citation statements)
references
References 27 publications
4
57
1
Order By: Relevance
“…Several human studies have demonstrated that long-term perceptual training or attentional shifts reorganize human somatosensory cortex (25)(26)(27)(28)(29)(30). However, although these studies demonstrated that the type of Euclidean distance between the N20-dipole location before and after coactivation for the test and the control finger (hemispheric difference, P Ͻ 0.05).…”
Section: Discussionmentioning
confidence: 72%
“…Several human studies have demonstrated that long-term perceptual training or attentional shifts reorganize human somatosensory cortex (25)(26)(27)(28)(29)(30). However, although these studies demonstrated that the type of Euclidean distance between the N20-dipole location before and after coactivation for the test and the control finger (hemispheric difference, P Ͻ 0.05).…”
Section: Discussionmentioning
confidence: 72%
“…On a speculative note, one might assume a plasticity-inducing process due to skill acquisition during repeated 2FT performance, which has been shown to coincide with a reduction of GABAergic motorcortical inhibition (Bütefisch et al, 2000; Ziemann et al, 2001; Floyer-Lea et al, 2006; Stagg et al, 2011a), adding to the disinhibitory effect of atDCS. Therefore, this might be interpreted as an indicator of immediate physiological homeostatic mechanisms, which limit the induction of plasticity to stabilize the excitation/inhibition balance and maintain network integrity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, repetition of movements has been suggested to result in motor memories in the primary motor cortex and probably other cortical areas that encode the kinematic details of the practiced movements (Classen et al, 1998; Butefisch et al, 2000; Stefan et al, 2005; Cross et al, 2009). Of particular interest, previous studies have demonstrated that motor memory can also be encoded by action observation and this form of action observation can enhance the effects of motor training on memory encoding, possibly through modulation of intracortical excitatory mechanisms (Stefan et al, 2005; Celnik et al, 2006).…”
Section: Functional Neuroplasticity In Skill Learning and Expertisementioning
confidence: 99%